Generation of Vaccine Candidate Strains That Antigenically Match Classical Swine Fever Virus Field Strains - Maya Kobayashi; Loc Tan Huynh; Saho Ogino; Lim Yik Hew; Miki Koyasu; Hikaru Kamata; Takahiro Hiono; Norikazu Isoda; Yoshihiro Sakoda (Vaccines)
Background: Classical swine fever virus (CSFV) is genetically categorized into three genotypes. A live-attenuated vaccine strain GPE−, currently used in Japan, belongs to genotype 1 and is genetically distinct from the field strains circulating in Japan, which belong to genotype 2. This study aimed to understand the antigenicity of recent field isolates in Japan and develop new vaccine candidates that antigenically match field strains. Methods: The serum samples of 20 pigs vaccinated with GPE− were subjected to a serum neutralizing test (SNT) using one of the field strains, CSFV/wb/Jpn-Mie/P96/2019 (Mie/2019). For the antigenic matching, vGPE−/HiBiT/Mie E2 was generated by replacing the viral glycoprotein E2, the main target of the neutralizing antibody, with that of Mie/2019. Additionally, vGPE−/HiBiT/Mie E2/PAPeV Erns was generated by further substituting glycoprotein Erns with that of pronghorn antelope pestivirus (PAPeV) since Erns is not important as a vaccine immunogen and can be replaced by that of other pestiviruses to provide an immunological marker. The efficacy of vGPE−/HiBiT/Mie E2/PAPeV Erns was further evaluated by the challenge experiments in pigs. Results: The SNT titers of serum sample against Mie/2019 were 6.1-fold lower than that against vGPE−. The generated recombinant viruses showed closer antigenicity to Mie/2019 than vGPE−. The challenge study confirmed that vGPE−/HiBiT/Mie E2/PAPeV Erns provided clinical and virological protection against a field CSFV equivalent to vGPE−. Conclusions: This study demonstrated that swapping the E2 encoding region with the prevalent field CSFVs is a promising strategy to achieve antigenic matching between the vaccine and field strains.